Building Hospitable Communities - Ferris, Elizabeth (Refuge: Canada’s Journal on Refugees, 2001)
Receiving communities play a critical role in determining whether refugees and other migrants will become full participating members of their host societies or whether they will remain on the margins. This paper reviews global trends which impact the receptivity of communities to refugees and migrants, including the growing public debate on migration, increasingly restrictive governmental policies, xenophobia and racism, public confusion, and increasing questions of citizenship and identity. This is followed by an examination of the roles played by national and local governments, the media, and civil society in creating communities which welcome newcomers, affirm diversity, and encourage full participation of all who live there.